2018
DOI: 10.1097/hcr.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Key Cardiopulmonary Exercise Testing Variables Following Cardiac Rehabilitation in Patients With Coronary Artery Disease

Abstract: Key markers of ventilatory efficiency and (Equation is included in full-text article.)O2 kinetics during CPX significantly improve following CR. Expanding the list of variables assessed via CPX may provide better resolution in validation of CR therapeutic efficacy in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
0
13
0
4
Order By: Relevance
“…Additionally, it was found that VO 2peak pred%, HR peak , AT, VO 2 /HR@AT, VE/VCO 2 @AT, VE/VCO 2 slope, and OUES were significantly better in the intervention group than in the control group after 6 months of intervention (P < 0.05). In a study of 142 patients with CHD, Popovic et al found significant improvement of patients in VO 2peak , VO 2 /HR@VO 2peak , VE/VCO 2 slope, and OUES after 3 to 6 months of cardiac rehabilitation [21]. Although changes of specific indicators are not exactly the same in those two studies, both of them demonstrated certain effects of monitored cardiac rehabilitation.…”
Section: Improvement In Exercise Tolerancementioning
confidence: 95%
“…Additionally, it was found that VO 2peak pred%, HR peak , AT, VO 2 /HR@AT, VE/VCO 2 @AT, VE/VCO 2 slope, and OUES were significantly better in the intervention group than in the control group after 6 months of intervention (P < 0.05). In a study of 142 patients with CHD, Popovic et al found significant improvement of patients in VO 2peak , VO 2 /HR@VO 2peak , VE/VCO 2 slope, and OUES after 3 to 6 months of cardiac rehabilitation [21]. Although changes of specific indicators are not exactly the same in those two studies, both of them demonstrated certain effects of monitored cardiac rehabilitation.…”
Section: Improvement In Exercise Tolerancementioning
confidence: 95%
“…cifras de colesterol total y LDL-c, mas no un incremento significativo en el HDL-c. Es probable que este hallazgo en nuestro estudio esté relacionado al hecho de que los pacientes ingresan al programa con medicación óptima para el tratamiento de dislipidemia y cifras cercanas o dentro de los rangos esperados. La capacidad funcional mejoró debido a la mejoría del consumo de oxigeno estimado a través de las pruebas (9) de esfuerzo. Popovic D. y cols.…”
Section: Resultsunclassified
“…La mejoría de la capacidad funcional estimada por METs fue significativa y esto se correlaciona con datos (9) (10) encontrados en otros estudios , lo que muestra el impacto del ejercicio sobre la performance (1) (12) cardiovascular del paciente .…”
Section: Agredecimientosunclassified
See 1 more Smart Citation
“…First, cardiovascular and respiratory failures are the most common dysfunctional organs in ICUs; therefore, cardiopulmonary rehabilitation can help recovery of the patients just survived through the critical illness. Second, cardiopulmonary rehabilitation has been proven its effect in improving ventilator efficiency and VO2 kinetics for patients with coronary artery disease, [ 28 ] in enhancing functional capacity, and quality of life for patients with heart failure, [ 29 ] in relieving dyspnea and improving exercise capacity for patients with chronic obstructive pulmonary diseases. [ 30 , 31 ] Third, the time frame of introducing rehabilitation is post-ICU discharge, not in the acute stage in the ICU.…”
Section: Discussionmentioning
confidence: 99%